2012
DOI: 10.1021/ie203017g
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Experiment and Numerical Analysis of a Modular Microcombustor with Silicon Carbide Porous Medium

Abstract: The use of porous media in combustion processes has been widely researched and investigated. In this paper, the effect of employing porous media on microcombustion was studied using numerical simulation. Simulated results demonstrated good agreement with the experimental results, and thus validated the model. Analysis has been carried out with dimensional analysis and basic theorem which incorporates the Biot number in an attempt to fundamentally understand the effects brought about by equivalence ratio, therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The highest efficiency of emitter with SiC as porous media is 0.182 when / = 0.8 as well, the other emission efficiency is 0.141 and 0.159 for mixture of / = 0.6 and / = 1.0. Similar outcome was also observed by Li et al [24] and Yang [22]. From the simulated results of temperature contours in 3, we can explain this phenomenon.…”
Section: Effect Of Hydrogen To Oxygen Equivalence Ratiosupporting
confidence: 89%
“…The highest efficiency of emitter with SiC as porous media is 0.182 when / = 0.8 as well, the other emission efficiency is 0.141 and 0.159 for mixture of / = 0.6 and / = 1.0. Similar outcome was also observed by Li et al [24] and Yang [22]. From the simulated results of temperature contours in 3, we can explain this phenomenon.…”
Section: Effect Of Hydrogen To Oxygen Equivalence Ratiosupporting
confidence: 89%
“…For a long time, chemical batteries have played a dominant role as the power source for MEMS and mobile electronic devices. However, there exist some major limitations such as negative environmental impacts, low power density and short usage time [1][2][3]. To overcome these limitations, there is an exacting need to develop an alternative and environmental friendly energy source with a higher power density.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a thermal equilibrium is equivalent to allowing heat transfer to occur instantaneously, which inherently precludes some important features of filtration combustion, for example, excess enthalpy combustion. Despite its deficiency in physics, the one-temperature model which was implemented in modeling micro-/meso-combustors has been found to be able to yield reasonable prediction of combustor wall temperature [23,24]. Under Assumption (7), the gaseous mixture and the solid matrix have one temperature (denoted as T g ), with the porous zone being represented by a lumped parameter, that is, the effective thermal conductivity (defined as k eff ).…”
Section: Modelingmentioning
confidence: 99%
“…Furthermore, an experimental study on the critical conditions corresponding to flame stability limits (blow-off and flashback) for different combustor configurations was carried out [22]. Chua et al [23] reported their simulation and experimental study on a planar micro-combustor fully filled with SiC foam, focusing on the wall temperature and emitter efficiency. Through CFD simulations, Pan et al [24] investigated H 2 -O 2 combustion in a cylindrical micro-combustor filled with SiC porous medium.…”
Section: Introductionmentioning
confidence: 99%